HANDHELD FINGER TECHNIQUE RELAXATION AND MUSIC THERAPY TO DECREASE ANXIETY IN PRE SECTIO CAESAREA PATIENTS - Arina Ma'rufa; kurniawati Puji Lestari; Elisa Elisa (JENDELA NURSING JOURNAL, 2019)
Background: There are still many pre-sectional caesarean patients who are increasing the number of surgical stressors that cause fear because they cause surgical action. In addition, patients must undergo psychological surgery during this operation are ignored and do not need to be treated because of psychological difficulties performed by the patient before surgery.Purpose: To find out the combination of the effect of handheld finger technique relaxation and music therapy to decrease of anxiety in patients with pre-Sectio Caesarea.Method: This research used a Pre-Experimental Design with a One-Group pre-post test design. The sampling technique uses accidental sampling. The number of respondents of Sectio Caesarea patients was 33 respondents. The instrument used was the Zung Self Anxiety Rating Scale (ZSARS) questionnaire.Results: The results of the study showed that the pre-sectional caesarean patients were given an intervention with a mild level of difficulty and after being given an intervention regarding the coverage, they were not worried. The Wilcoxon test results showed a p value of 0,000 (p 0.05).Conclusion: The combination of handheld finger relaxation techniques and music therapy has an effect to decreasing anxiety in pre-sectional caesarean patients